Why resource‐based theory's model of profit appropriation must incorporate a stakeholder perspective - Barney, Jay B. (Strategic Management Journal, 2018)
Research Summary: Using arguments derived from transactions cost economics and incomplete contract theory, this article shows that the assumption that shareholders are a firm's only residual claimants is logically inconsistent with resource‐based theory's model of profit generation. It follows from this conclusion that resource‐based theory's model of profit appropriation must incorporate a stakeholder perspective. Some theoretical and empirical implications of this conclusion for resource‐based theory's model of profit generation, profit appropriation, the role of managers and entrepreneurs in resource‐based theory, and how conflicting interests among stakeholders can be resolved are all discussed. Finally, some continuing differences between stakeholder theory and incorporating a stakeholder perspective into resource‐based theory's model of profit appropriation are also discussed. Managerial Summary: Some argue that since shareholders are the only stakeholder who have a claim on a firm's profits, managers should focus only on maximizing shareholder wealth. Not only will this satisfy shareholders, it will also satisfy a firm's other stakeholders, since—in principle—these other stakeholders get paid before shareholders. This article shows that this logic is deeply flawed. In particular, it shows that if the only stakeholder who has a claim on a firm's economic profits is shareholders, then—in most competitive settings—a firm will not be able to attract the kinds of resources it needs to generate these profits. To attract the kinds of resources that can generate profits, managers must recognize that stakeholders, besides shareholders, have claims on the profits that their resources help generate. This, in turn, suggests that managers seeking to generate economic profits must adopt a stakeholder perspective in how they manage their firm. This article explores the managerial implications of this conclusion.